Theoretical and morphological mechanisms of pathogenesis of atherosclerosis and it’s complifications. New ways of their precaution and treatment - Fedchenko N.P.; Fedchenko N.N. (Морфологія, 2009)
A three-stage algorithm of morphogeny of atherosclerosis is established: overendothelial, subendothelial and unendothelial stages. On the first stage physiological transport of endothelial predecessors and lipid components of SMOPEN (Specific MOlecular Protector of ENdothelium) from lipotkanella to vessel’s endothelial layer breaks due to the set of factors. Due to this molecular protector extends and becomes loosened in its superficial departments, where blood corpuscles get stuck. On perimeter of a vessel SMOPEN becomes asymmetric and fragmentary. As a result pink gelatin-similar plaques are formed. With time these plaques become hyalinizated (overendothelial stage). Because of the block of an output of lipid component into SMOPEN, it gathers in the arterial’s intima and forms lipid nucleus of the plaque (subendothelial stage). Endothelial layer under gelatin-similar plaque disappears because of transformation of its cells into fibroblasts. This stage is accompanied by merge of a blood vessel’s wall with hyalinizated SMOPEN plaque, which ends with it’s fibrotization. As a result the hyalin-fibrous cover for lipid nucleus is formed (unendothelial stage). The increase of local plaque’s protrusion into blood vessel’s lumen results in SMOPEN infarct or through cavitation effect leads to thrombus formation or gas embolism. For preventive maintenance and treatment of these conditions it is necessary to provide sufficient transport of endothelia’s predecessors and SMOPEN’s lipid components, to dissolve reversible gelatin-similar plaques, avoid cavitation, apply pres-sure chamber to removal gas emboli from the fine vessels.